Application and prospect of novel nanomedicine in cancer therapy - Qiao, Lijie (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the rapid development of nanotechnology, the application of new nanodrugs in cancer treatment has gradually become a research hotspot. In this paper, we explore the design principles, preparation methods and their anticancer effects in vitro and in vivo, and explore potential clinical applications. The results show that nanomedicine improve the therapeutic effect and reduce the side effects by achieving accurate delivery and controlled release of drugs, providing a new solution for cancer treatment. In terms of design principles, nanomdrugs mainly make use of unique properties such as small size effects, surface effects and quantum size effects of nanomaterials to combine drug molecules with nanocarriers to achieve precise delivery and controlled release of drugs. In terms of preparation methods, physical, chemical and biological methods are used to prepare nanoscale drugs with different morphology and structures. In vitro and in vivo experiments showed that nanomedicines can significantly increase the concentration of the drug in the tumor cells, enhance the therapeutic efficacy, and reduce the toxicity to normal tissues. However, nanomedicine still face many challenges in the field of cancer therapy. Looking ahead, with the continuous advances in nanotechnology, it is reasonable to believe that nanomedicine will play a greater role in the field of cancer therapy. Through in-depth study of the mechanism of action of nanomedicine, optimizing the preparation process, improving the precision of the controlled drug release system, and focusing on the biological safety issues, we are expected to bring safer and more effective treatment methods for cancer patients. At the same time, the combined application of nanomedicine and other therapeutic means such as immunotherapy and gene therapy will also become a research hotspot in the future, providing more comprehensive and personalized treatment options for cancer treatment.